Project-Based Learning for English Diploma Program Students: Implementation and Challenges in Online Learning - Indah Puspitasari; Kristianto Setiawan (Tell : Teaching of English Language and Literature Journal, 2022)
The central goals of this study are to see the implementation of Project-Based Learning for English diploma program students, to see the students' perceptions toward the implementation of project-based learning, and to see the challenges of its implementation in online learning. The research method is a descriptive qualitative method that used Stoller and Simpson theories to analyze the implementation of Project-based Learning in online learning. The results of this study show that 77.1% of respondents are satisfied with the implementation of project-based learning. They also obtained 82.07, which means the students are able to achieve the learning outcome very well. There are some challenges in implementing project-based learning in the pandemic era. They needed autonomous learning methods, especially in mastering language skills, knowledge, and IT skills. However, to achieve learning outcomes and to solve the problems, the students independently discussed and worked together in their group to finish their project. The effect of this process, students are more independent, critical, communicative, and creative in working on the project. Based on the positive findings, project-based learning becomes one of the alternative methods for assisting English diploma program students in acquiring 4Cs.